MAKNA TRADISI NGANTUNG BUAI BAGI MASYARAKAT DESA SERI KEMBANG II KECAMATAN PAYARAMAN KABUPATEN OGAN ILIR - Reza Aprianti (Universitas Bunda Mulia, 2021)
The Ngantung Buai tradition is a birth tradition carried out by the community of Seri Kembang II Village, Payaraman District, Ogan Ilir Regency, South Sumatra Province to inaugurate the name of a newborn baby after the umbilical cord of a newborn is released. The implementation of the Ngantung Buai tradition has hidden symbols as seen in signs or tools used in its implementation that are known to the people of Seri Kembang II Village. The purpose of this study is to analyze the implementation process of the Ngantung Buai tradition, the meaning of the Ngantung Buai tradition for the people of Seri Kembang II Village and to analyze the semiotic meaning of Charles Sanders Peirce against the Ngantung Buai tradition in the Seri Kembang II Desa Kembang II uses a qualitative method by understanding the phenomena experienced by research objects in the field. Based on an analysis of Charles Sanders Pierce's Semiotic theory in the form of views based on representamen, objects and interpretants, this tradition has symbols whose meanings of prayer and hopes are intended for newborns with good intentions and purposes for the baby's life.